Pengaruh Perubahan Tutupan Lahan Terhadap Emisi GRK pada Wilayah Cepat Tumbuh di Kota Semarang - Danar Dewa, Dimas; Sejati, Anang Wahyu (Jurnal Penginderaan Jauh Indonesia, 2019)
Effects of Land Cover Changes on GHG Emissions in Fast-Growing Areas in Semarang City This article aims to convey the results of the calculation of greenhouse gas (GHG) emissions from land cover change factors. The method used is spatio-temporal with remote sensing supported by Support Vector Machine classification techniques from Deztsaka Tools. The results obtained were the most significant changes in land cover occurred in the forest land cover class which decreased by 1515.29 Ha (21%). Carbon reserves in fast-growing areas have decreased by 90,741.06 tons (68.58%) and 22% of the area has released GHG emissions in the amount of more than 1000 tons. This phenomenon requires serious attention because land cover change is very significant, so that control efforts through spatial planning policies are absolutely necessary.